Analisis Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Loyalitas sebagai Variabel Intervening - Pohan, Hamsa Aulia; Rizky, Chaerul (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study was conducted to determine the effect of work discipline and work environment on employee performance with loyalty as an intervening variable at the Population and Family Planning Control Office of Tebing Tinggi City. The purpose of this study was to determine how much influence the variables of work discipline and work environment have. The purpose of this study was to determine how much influence the variables of work discipline and work environment have on employee performance with loyalty as an intervening variable. This study was conducted using a quantitative approach with an analysis method, namely path analysis. The sample in this study was 40 people. The data collection method used was by using instruments and also field observations and data testing using the SPSS Ver.20.00 application